2015
DOI: 10.1007/s00210-015-1152-z
|View full text |Cite
|
Sign up to set email alerts
|

Zerumbone, a ginger sesquiterpene, induces apoptosis and autophagy in human hormone-refractory prostate cancers through tubulin binding and crosstalk between endoplasmic reticulum stress and mitochondrial insult

Abstract: Zerumbone, a natural monocyclic sesquiterpene, is the main component of the tropical plant Zingiber zerumbet Smith. Zerumbone induced antiproliferative and apoptotic effects against PC-3 and DU-145, two human hormone-refractory prostate cancer (HRPC) cell lines. Zerumbone inhibited microtubule assembly and induced an increase of MPM-2 expression (specific recognition of mitotic proteins). It also caused an increase of phosphorylation of Bcl-2 and Bcl-xL, two key events in tubulin-binding effect, indicating tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 48 publications
4
15
0
Order By: Relevance
“…In a study by Chan et al, ginger extract could destroy prostate cancer cells at the cellular level. Such an anticancer effect was achieved through binding to tubulin and establishing a connection between endoplasmic reticulum stress and mitochondrial damage (45). A similar result was reported by Saha et al (46).…”
Section: Discussionsupporting
confidence: 58%
“…In a study by Chan et al, ginger extract could destroy prostate cancer cells at the cellular level. Such an anticancer effect was achieved through binding to tubulin and establishing a connection between endoplasmic reticulum stress and mitochondrial damage (45). A similar result was reported by Saha et al (46).…”
Section: Discussionsupporting
confidence: 58%
“…It arrests treated cells in the G 2 /M-phase of the cell cycle in a time (24, 48, and 72 h) and concentration (26, 42, and 57 µM) dependent manner, followed by apoptosis [ 125 ]. Chan et al found that 30 µM zerumbone had anti-proliferative activity to PC-3 and DU-145 prostate cancer cell lines inducing a G 2 /M-phase arrest at 8 h, and increased the levels of PH3, cyclin B, and MPM2 expression, a mitotic marker [ 126 ]. It was shown that zerumbone caused a mitotic arrest by targeting tubulin/microtubules and disrupting microtubule dynamics, which led to the formation of aberrant monopolar and multipolar spindles [ 126 ].…”
Section: Anti-mitotic Activities Of Sesquiterpenesmentioning
confidence: 99%
“…Chan et al found that 30 µM zerumbone had anti-proliferative activity to PC-3 and DU-145 prostate cancer cell lines inducing a G 2 /M-phase arrest at 8 h, and increased the levels of PH3, cyclin B, and MPM2 expression, a mitotic marker [ 126 ]. It was shown that zerumbone caused a mitotic arrest by targeting tubulin/microtubules and disrupting microtubule dynamics, which led to the formation of aberrant monopolar and multipolar spindles [ 126 ]. The authors described other effects upon cells treated with zerumbone, which included endoplasmic reticulum stress and mitochondria-mediated apoptosis.…”
Section: Anti-mitotic Activities Of Sesquiterpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zerumbone is a natural monocyclic sesquiterpene from Zingiber zerumbet Smith. It has been investigated that zerumbone may induce apoptosis and autophagy in PC-3 and DU-145 cells through ER stress induction and mitochondrial dysfunction [ 108 ].…”
Section: The Natural Occurring Compounds Interact With Er Stressmentioning
confidence: 99%